The influence of massage with bees product propolis on the treatment of locomotor system traumas - Valuziene, N. (Education. Physical training. Sport, 1999)
In the article the application of bees product propolis (pitch) in the rehabilitation of persons after joints traumas and bone fractures is analysed. Results: In the case of the examinees massaged with propolis the limb swelling quieted down quicker, the amplitude of joint movements increased more. In most cases the results were statistically reliable. We explain this effect by versatile propolis biologic activity and recommend to apply it while doing massage after joints traumas and bone fractures especially while massaging the sportsmen who have undergone traumas and also while massaging the disabled whose tissues are hardened, sometimes painful. Massage with propolis could help to improve their general state.